Opportunities and challenges of multi-loop aquaponic systems - Goddek, Simon (Wageningen University, 2017)
Unicellular, photosynthetic microalgae and cyanobacteriaare potential new protein sources for both food and feed. Variations between these sources are reflected in chemical variations (e.g. in the chemical composition) and in structural variation (e.g. in cell wall robustness). The aim of this thesis was to understand how chemical and structural variations between unicellular photosynthetic sources affect the application of unicellular protein as techno-functional ingredients and as a fish feed ingredient.